RETRACTED: Computational fluid dynamics, a building simulation tool for achieving sustainable buildings. (May 2016) - Anand, Y.; Gupta, A.; Tyagi, S.K.; Anand, S.
Abstract : This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy ). This article has been retracted at the request of the Editor-in-Chief. The authors have plagiarized part of a paper that had already appeared in Journal of Building Performance Simulation, 4 (2011), 157–184, 10.1080/19401493.2010.513740. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.